THE KINGDOM OF ACEH DARUSSALAM AFTER THE EXILING OF SULTAN MUHAMMAD DAUD SHAH (1906-1942) - Nita Juliana; Anwar Daud; Asmanidar (Indonesian Journal of Islamic History and Culture, 2022)
This study aims to examine the extent of Dutch intervention in destroying Aceh's sovereignty, and what efforts were attempted by Sultan Muhammad Daud Syah in restoring the sovereignty after his exile. The methods used are heuristics, critical interpretation, and historiography. The results showed that the Dutch violated the laws of war by kidnapping the two consorts and their children so that the Sultan would surrender. The contribution of Sultan Muhammad Daud Syah in his exile to restore Aceh's sovereignty was to provide financial support and hold communication with the fighters in the interior. In addition, he also asked for reinforcements from foreign powers (Japan) to expel the Dutch colonialists in Aceh.